Novel global optimization approach for the simultaneous design of heat exchangers in heat exchanger networks constrained by pressure drop - Hajabdollahi, Hassan; Costa, André L.H.; Bagajewicz, Miguel J. (Computers & chemical engineering, 2025)
We address the simultaneous globally optimal basic design of shell-and-tube heat exchangers interconnected in a HEN, where the total pressure drop of the streams that pass through several exchangers is limited to a maximum. We explore the optimal distribution of the available pressure drop in each stream among different heat exchangers, instead of the traditional procedure based on individual values of available pressure drop. The approach is useful in the context of HEN synthesis based on network structure enumeration when the design of the equipment is embedded in the algorithm. The objective is to obtain the optimal geometry of each exchanger, such that the total area or investment cost is minimized subject to the collective pressure drop constraints. The design variables for the shell-and-tube heat exchangers include all typical geometric dimensions. The novel global optimization approach builds an integer linear optimization model (ILOM), which is solved using an integer linear programming method (ILP). The ILOM involves only feasible heat exchanger candidates, obtained using Complete Set Trimming. The procedure was applied to two test cases involving 8 and 23 heat exchangers, respectively, each exchanger having 12,852,000 initial candidate geometries. The computational times for this task are below one hour for the two studied cases when implemented in MATLAB. Results for optimizing using the total annualized cost (CAPEX+OPEX) as an objective function and without pressure drop constraints are also presented for comparison.